Growth and structural discrimination of cortical neurons on randomly oriented and vertically aligned dense carbon nanotube networks - Nick, Christoph; Yadav, Sandeep; Joshi, Ravi; Thielemann, Christiane; Schneider, Jörg J. (Beilstein Journal of Nanotechnology, 2014)
The growth of cortical neurons on three dimensional structures of spatially defined (structured) randomly oriented, as well as on vertically aligned, carbon nanotubes (CNT) is studied. Cortical neurons are attracted towards both types of CNT nano-architectures. For both, neurons form clusters in close vicinity to the CNT structures whereupon the randomly oriented CNTs are more closely colonised than the CNT pillars. Neurons develop communication paths via neurites on both nanoarchitectures. These neuron cells attach preferentially on the CNT sidewalls of the vertically aligned CNT architecture instead than onto the tips of the individual CNT pillars.
Keywords: carbon nanotube; chemical vapour deposition; interface; neuron; scaffold